Indecision-inaction phenomenon: development and validation of the indecision-inaction phenomenon scale (IIPS) - Ferland, Missy, author; Dik, Bryan, advisor; Amberg, Marti, committee member; Prasad, Joshua, committee member; Peila-Shuster, Jackie, committee member (Colorado State University. Libraries, 2025)
Many people are familiar with the experience colloquially known as "analysis paralysis," yet this concept has not precisely been defined, much less operationalized via a measurement instrument. The purpose of this study is to develop a scale to operationalize the latent variable "analysis paralysis," referred to in a more sensitive manner as "indecision-inaction phenomenon," and to establish initial psychometric support for its scores. Indecision-inaction phenomenon is a system of maladaptive cognitive processes that interfere with task completion in individuals, in which excessive deliberation without progression toward execution paradoxically prevents decision-making or goal-oriented action. This study proposed and tested a three-factor model for the latent variable indecision-inaction phenomenon, comprising the perceived choice paradox dimension, the irrational prospection dimension, and the unfulfillment dimension. An item pool was generated, and subject matter expert feedback was integrated to enhance content validity by refining items. A Qualtrics survey was administered to a student sample, including items in the proposed scale as well as several other established scales to explore initial validity evidence. Exploratory Factor Analysis (EFA) was conducted to investigate the underlying factor structure of the proposed items and inform subsequent scale revisions. The EFA revealed a three-factor structure reflecting the dimensions IIP- Perceived Choice Paradox, IIP- Irrational Prospection, and IIP- Unfulfillment, as hypothesized. Next, this factor structure was rigorously tested and confirmed using Confirmatory Factor Analyses (CFA), again demonstrating a good fit for the three-factor model. Finally, initial reliability and validity evidence for the scale was explored using correlations with scores on scales measuring established criterion variables, generally revealing relationships in expected directions and magnitudes with other constructs. This study offers a framework and instrument— the Indecision-Inaction Phenomenon Scale (IPPS)— for understanding and measuring the experience of indecision-inaction phenomenon, which may be used in future research on maladaptive cognitive processes.
Keywords: decision-making; indecisiveness; procrastination; indecision; analysis paralysis; neuroticism